THE ROLE OF TECHNOLOGY IN EDUCATION (Ustozlar uchun, 2025)
This article covers the topic “The Role of Technology in Education” and analyzes the importance, capabilities, and impact of technology on the quality of education in the modern educational process. Digital technologies provide learners with quick access to a wide range of information resources, interactive lesson formats, virtual laboratories, online platforms, and artificial intelligence-based learning systems to effectively acquire knowledge. Technologies also allow teachers to optimize the teaching process, automate assessment, diversify educational materials, and adapt them to the individual needs of students. In addition, digital tools develop students' independent learning skills, form creative thinking, and analytical competencies.